2003
DOI: 10.1099/vir.0.19095-0
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E2- and L1-specific serological and T-cell responses in women with vulval intraepithelial neoplasia

Abstract: Human papillomavirus type 16 (HPV-16)-associated vulval intraepithelial neoplasia (VIN) is frequently a chronic, multifocal high-grade condition with an appreciable risk of progression to vulval cancer. The requirement to treat women with VIN has recently stimulated the use of immunotherapy with E6/E7 oncogene vaccines. Animal models have shown that E2 may also be a useful vaccine target for HPV-associated disease; however, little is known about E2 immunity in humans. This study investigated the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Analysis of HPV16 L1 peptide-specific immunity in patients with HPV161 CIN II/III also revealed that the vast majority of these subjects displayed strong type 1 T-cell immunity against this antigen, corroborating the data of others. [21][22][23]34 In addition, this study shows that strong HPV16 L1 peptide-specific type 1 T-cell immunity is also present in the majority of patients with an HPV161 cervical carcinoma. These responses were covering a broad range of peptides within L1, suggesting that during persistent or repeated exposure to HPV16 L1, the immune system maximizes its efforts to counter the viral challenge.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Analysis of HPV16 L1 peptide-specific immunity in patients with HPV161 CIN II/III also revealed that the vast majority of these subjects displayed strong type 1 T-cell immunity against this antigen, corroborating the data of others. [21][22][23]34 In addition, this study shows that strong HPV16 L1 peptide-specific type 1 T-cell immunity is also present in the majority of patients with an HPV161 cervical carcinoma. These responses were covering a broad range of peptides within L1, suggesting that during persistent or repeated exposure to HPV16 L1, the immune system maximizes its efforts to counter the viral challenge.…”
Section: Discussionmentioning
confidence: 91%
“…[21][22][23]33,34 To obtain more detailed information about the magnitude, specificity and functionality of T-cell responses against HPV16 L1, we incubated PBMC isolated from the blood of a group of 20 healthy donors with an overlapping set of 30-mer peptides covering the entire HPV16 L1 sequence and tested T-cell reactivity by IFNg ELISPOT assay. In addition, PBMC were incubated with HPV16 E6 peptides to relate the reactivity against L1 with our previous findings for early antigens.…”
Section: Hpv16 L1-specific T-cell Responses In Healthy Donorsmentioning
confidence: 99%
“…This screening strategy might have favored the selection of hybridoma clones producing MAbs that preferentially recognize linear epitopes. However, the GST-L1 capture ELISA was previously demonstrated to be equivalent to VLP ELISA (19,46). Moreover, Rizk et al previously showed that MAbs raised against VLPs and that recognize conformation-dependent epitopes also bind to GST-L1 fusion proteins, suggesting that they display most conformational and neutralizing epitopes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have concentrated on measuring HPV16 E6-and/or E7-specific immune responses, since these antigens are continuously expressed throughout the full spectrum of HPV-associated disease development [32]. More recently, E2-specific T-cell responses have been reported in patients and healthy volunteers alike, although the relationship between the measured immunity and disease outcome is unclear [25,33,34]. Taking all of these results together, it appears that the specific type(s) of cellular immunity that an individual mounts in response to an HPV infection may influence its outcome.…”
Section: Natural Immune Responses In Hpv-associated Diseasementioning
confidence: 98%